Effect of problem-based learning integrated with Contextual Teaching and Learning on kitchen utensil learning outcomes - Trisna Atmadinata; Fadhilah Fadhilah; M. Giatman; Kasmita Kasmita (Global Econedu, 2026)
This study aimed to examine the effect of the Problem-Based Learning (PBL) model integrated with Contextual Teaching and Learning (CTL) on students’ cognitive learning outcomes in the Kitchen Utensil topic among Grade X Culinary students at SMK Negeri 3 Solok. A quantitative approach with a quasi-experimental non-equivalent control group design was employed. The sample consisted of 62 students divided into an experimental group (n = 31) and a control group (n = 31). Data were collected through pretest and posttest achievement tests and analyzed using descriptive statistics, Independent Samples t-test, Paired Samples t-test, N-Gain analysis, and Cohen’s d effect size. The findings revealed a significant difference in posttest scores between the experimental and control groups (t = 3.020, p = 0.004). The experimental group achieved a higher mean score (79.44) than the control group (72.58). Furthermore, students in the experimental group demonstrated significant improvement from pretest to posttest (t = -13.902, p < 0.001), with an N-Gain score of 0.39 and a very large effect size (d = 2.497). The PBL-based CTL model was effective in improving students’ cognitive learning outcomes and can serve as an innovative instructional approach in vocational culinary education.